Critical Junctures and Conditions of Change: Exploring the Fall of Prison Populations in US States. (February 2019) - Karstedt, Susanne; Bergin, Tiffany; Koch, Michael
State prison populations in the United States have been regularly declining since 2009, and, at the end of 2014, the combined federal and state prison population was at its lowest level since 2005. Criminologists were caught by surprise by this development in the country that epitomized contemporary 'mass incarceration'. Their theoretical accounts were steeped in a 'punitive worldview' that left no space for the stabilization and eventual decline in mass incarceration in the United States. This article focuses on policy processes, rather than structural conditions, as drivers of penal change. The article begins with an overview of theories of punishment and their shortcomings. The framework that guides our study is based on the concept of 'critical junctures', which are seedbeds of long-term transformative change that present opportunities and constraints for actors in the penal field. The empirical research presented here analyses the adoption of legal reforms aimed at reducing mass incarceration by the 50 US states. We find that a trifecta of conflicting actors – legal, political and public – accounts for the complex and sometimes contradictory ways in which states move towards penal reform.